Behavior patterns of the water quality of water ecosystems and their relationship with the occupation of the territory in the Chocó Biogeográfico - Vargas Porras, Lady (Journal BioEtnia, 2015)
With the data obtained in environmental characterizations performed in 12 basins distributed altitudinally in the Chocó Biogeographic region, a principal component analysis (PCA) and dispersion charts were applied, which allowed to establish a pattern behaviour of the quality of the water and to evaluate the the relationship between physicochemical varia- bles, biological and social. The PCA yielded 5 components that explained 90% of the variability of the data. Three of these components indicated strong relationships between nutrient concentration and the number of macroinvertebrate individuals, in addition to altitude, conductivity, pH and the presence of mineral spills and anthropic wastes, as well as between population level and concentration fecal coliforms, fats and oils. The results allowed to conclude that the pattern of behavior of the water quality in the region is de- termined not only by the population level present in the area of influence of the water sources, but by a combination of elements that include the type of productive practices developed, the state of the basic sanitation systems and the altitudinal distribution of the occupation of the territory that is a cultural characteristic of the region.